Municipal Solid Waste Management in an Urban Setting in India: A Case Study of Prayagraj City - Dubey R.; Rathore D.; Dwivedi A. (My University, 2025)
The aim of this study was to evaluate the current state of the procedure for managing municipal solid waste (MSW) in Prayagraj City, India. The data for this study were obtained from various secondary sources, including government records, publications, research papers, and web sources. A detailed study was conducted on solid waste generation, collection, transportation, and disposal methods through personal interviews with the sanitary officers, staff, and people of Prayagraj Municipality. The study findings revealed that most of the city's waste collection frequency is irregular. MSW comprised compostable matter (41.57%), ash, fine earth, and others (40.52%), the rest is recyclable (17.91%). However, a considerable amount of waste continues to go uncollected or not disposed of properly, which presents substantial risks to the environment and public health. Ragpickers are essential in reintegrating discarded plastic into the value chain, preventing it from ending up in landfills and preventing long-term environmental hazard. This paper also explores the potential of waste processing methods like composting and bio-methanation, highlighting the importance of an integrated waste management system for promoting sustainable urban living. The research emphasises the importance of having a comprehensive waste management system incorporating improved waste segregation at its origin, adopting scientific processing techniques, and establishing sanitary landfills. © 2025, Iquz Galaxy Publisher. All rights reserved.